Multi‐layered tissue models in patient‐specific simulations of aortic dissection. Issue 1 (14th December 2021) - Schussnig, Richard; Bäumler, Kathrin; Fries, Thomas-Peter
Abstract: In aortic dissections blood flows not only in the regular, true lumen but also between separated lamellae within the media of the aortic wall, in the so‐called false lumen. Both lumina are separated by a dissection membrane, which may move substantially during the cardiac cycle, linking blood flow and vessel deformation. We employ strongly coupled fluid‐structure interaction simulations incorporating an anisotropic, fiber‐reinforced, hyperelastic continuum including layer‐specific tissue parameters.